Investigation on the Application of Taylor Impact Test to High-G Loading - Juncheng, Li; Gang, Chen; Yonggang, Lu; Fenglei, Huang (Frontiers in Materials, 2021)
The Taylor impact test is characterized by high impact energy and good repeatability and thus has potential for application to high-g loading experiments for large-mass components. The feasibility of performing high-g load impact testing of a missile-borne recorder by conducting a Taylor impact test was studied by combining simulation analyses with experimental verification. Based on the actual dimensions of the missile-borne recorder, an experimental piece was designed based on the Taylor impact principle. The impact loading characteristics of the missile-borne recorder were then simulated and analyzed at different impact velocities. In addition, the peak acceleration function and the pulse duration function of the load were fitted to guide the experimental design. A Taylor-Hopkinson impact experiment was also conducted to measure the impact load that was actually experienced by the missile-borne recorder during the impact process and the results were compared with the results of strain measurements on the Hopkinson incident bar. The results showed that the peak value of impact load, the pulse duration and the waveform of the actual experimental results were in good agreement with the results predicted by the simulations. Additionally, the strain data measured on the incident bar could be used to verify or replace the acceleration testing of the specimen to simplify the experimental process required. Based on the impact velocity, high-g loading impact was achieved with peak values in the 7000g–30000g range and durations of 1.3 ms–1 ms, and the waveform generated was a sawtooth wave. The research results verified the feasibility of applying the Taylor impact test method to high-g loading tests.